DEVELOPMENT OF EMOTİONAL İNTELLİGENCE İN STUDENTS AND THE FACTOR OF EMOTİONAL SELF-REGULATİON - Simara, Hasanova; Fatima, Huseynova; Sabina, Mahmudova; Raya, Islamli (Health and Society, 2026)
The article explores the relationship between the level of emotional intelligence of students and their self-regulation skills. The study was conducted with the participation of 132 students, quantitative and correlation design was used. The Bar-On model was used to measure emotional intelligence, and the Self-Regulation Questionnaire technique was used to assess self-regulation.The results showed that there is a positive and statistically significant relationship between the level of emotional intelligence and self-regulation skills. A high level of emotional intelligence is characterized by more effective management of emotional abilities and assimilation of behavior patterns appropriate to the situation. The study revealed that the components of emotional intelligence, especially emotion management and stress resistance, have a closer connection with self-regulation.The results of the study indicate that the development of emotional intelligence contributes to more adaptive behavior of students both in the academic and social environment. In this regard, the development and application of psychological interventions aimed at the development of emotional intelligence are considered expedient.